(untitled) (Medical Forum Monthly, 2024)
Objective: To determine the effects of medical study on sports activities of medical students. Study Duration: cross sectional study Place and Duration of Study: This study was conducted at PMC in Rawlakot AJ&K from March 2013 5o March 2015. Materials and Methods: This study obtained data (88 persons) in a purposive sample from the entire second year class using a structured self-administered questionnaire, with 88% response rate. Results: Out of total 88 respondents, 63 girls (72%) and 25 boys (28%) with a mean age of 19 participated. More than 80% respondents had many friends, 81% girls and 36% boys didn’t have time to meet them ((p<.000). Around 89% girls and 68% boys didn’t have time to play ((p.029), 40% hostelite and non-hostelite could play (p<.991), and 76% boys and 65% girls perceived burdensome medical study which deprived them from regularly meeting their friends and participating in these activities. Conclusion: Findings of this study have broader implications for furnishing academic environment in medical institutions of Pakistan more conducive, supportive and effective. Medical institutions should review their curriculum and teaching/learning schedules and try to redesign their educational programs keeping a balance between study load and sports activities of a medical student. Students should also be encouraged to set their priorities and try to ensure this balance.